Processos espaciais e geografia cultural - Paul Claval (Confins)
As a consequence of the cultural turn, the cultural approach focused on the spatial processes in which culture is involved. Hence a widening and deepening of cultural geography. (i) Culture is partly shaped by the modes of transmission responsible for its passing down from one generation to the next. They stress more or less know-hows and knowledge (i.e. intelligence) and emotivity and imagination (i.e. imaginaries). (ii) Culture is equally shaped by the debates and opinions it induces, the genesis of identities, the dynamics of imitation or distinction and the process and conflicts of civilization or decline they initiate. (iii) Culture is combined with other processes when it deals with matter or life, produces artefacts, deals with nature, is applied to the human body, analyses the role of senses and shapes the landscape. (iv) It contributes to transform social life into a show and its setting into a stage. In its present form, cultural geography completes by a socio-cultural approach the older